Análise da Variabilidade Térmica em Zonas de Bordas Florestais com Interface Urbana no Maciço da Tijuca Rio de Janeiro-RJ - Figueiró, Adriano S. (2007)
The goal of this research was to identify and assess the termic gradientgenerated by the spread of the brim effect on the city-forest interface in twoselected areas with different degrees of urban density ( Catrambi area – high174 Ciência e Natura, UFSM, 29(2): 173 - 186, 2007density, and Soberbo area – low density), on the edge of Floresta da Tijuca- Rio de Janeiro (RJ). The working hypothesis was that the increase inurban pressure on the city-forest interface zone edge about a change in thedynamics of the edge effect, accelerating its propagation, especially in regardto termic changes, with a direct impact on the system’s functionality. Fielddata gathered from three transects measuring 100 meters in each area (with5 100 m2 patches in each transect). The results of this research point outthat the difference in urban density between the two researched areas bearsa significant influence on the propagation of the edge effect (with differenceuntil 3,5°C in the transect border-center) , but not directly, since it does sothrough an increase in the density of tracks and pathways internal to theedge area.